KONTRIBUSI PENDAPATAN SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Mohammad Dendi Abdul Nasir; Nunuk Khomariyah (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
Locally-generated revenue is a regional income from various businesses carried out by the Regional Government to finance regional activities and development. One of the potential sectors is the tourism sector. It is known that during the 2013-2018 tourism sector revenue in the Province of DIY has always increased. According to this matter, it is necessary to analyze several factors that touch the acceptance of the tourism sector in DIY Province. This study aims to analyze the influence of the variable the number of tourists, the number of hotels, and the number of tourism objects to Locally-generated Revenue in the Province of DIY. The data of this research are secondary data. The analytical tool used in this study is panel data. Partially, the number of tourists and the number of hotels have a significant influence, while the number of tourist objects has no effect on the locally-generated revenue from the tourism sector.